THE EFFECTS OF DIRECTED READING ACTIVITY STRATEGY (DRTA) IN DESCRITIVE READING TEXTS - Akmal Akmal (Smart Education, 2018)
This study aims to investigate the implemetation of Directed Reading Thinking Activity (DR-TA) in enhancing students’ reading comprehension at Muhammadiyah Senior High School in Kisaran in Academic Year 2016/2017. The process of DR-TA includes predicting, reading, and proving. This study focused on the quantitative research design by using the experimetal design. In this study, the research is done pre-test and post-test. As the theories of strategies guide in the process, the DRTA teaches students to determine the purpose for reading and make adjustments to what they think will come next based on the text. The findings of research show that the students’ reading comprehension has increased after applying Directed Reading Thinking Activity( DR-TA) when the experumental class students got the treatment in a few meetings. By using this strategy, the students can do the activity more actively and develope their prior knowledge of a topic/content of the text to be read, hypothesize about what might be addressed in the text, and establish meaningful purposes for reading the text.